Rekonstruksi Etnofisika pada Proses Pembuatan dan Pertunjukan Gendang Beleq Masyarakat Sasak Lombok: Analisis Getaran, Gelombang Bunyi, dan Resonansi - Nur Septiana; Hotimatul Sapitri; Husnul Aini; Baiq Aryani Novianti; Fartina; Tarpin Juandi; Khaerus Syahidi (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2025)
This study aims to reconstruct the local knowledge of the Sasak people in the process of making, tuning, and performing Gendang Beleq into a physics concept. The study used a qualitative approach with a focused ethnographic design at the Den Nune Sapu Jagat Art Studio, Masbagik, East Lombok. Informants consisted of a cultural figure and a Gendang Beleq player who were selected purposively. Data were collected through observation, semi-structured interviews, and documentation, then analyzed through data condensation, data presentation, and verification of conclusions with emic and etic perspectives. The results showed that the choice of wood, body and cavity size, membrane type and tension, striking position, and playing pattern are related to material properties, impulsive force, membrane vibration, sound waves, natural frequency, damping, and resonance. Gendang Beleq has conceptual and contextual suitability to be developed as a local culture-based physics learning resource. Further research is needed to test its acoustic characteristics and learning effectiveness.